Determining the efficacy of low retention thresholds of chromated copper arsenate preservatives for aboveground wood protection against termites - Khoo Li Mei., Wendy (Universiti Malaysia Sarawak (UNIMAS), 2010)
The main aim of this study is to determine the low retention thresholds of pressure treated chromated copper arsenate (CCA) preservatives on three different Malaysian hardwood timber species against termites, continuing from previous thesis study by Lui (2009). Three timber species being used were Acacia mangium (Brown salwood), Shorea macrophylla (Engkabang jantong), and Xyopia sp. (Ako). The pressure treatment of CCA onto the wood blocks was based on the full cell process. Artificial leaching was carried out as a simulated ageing process to leach the CCA. Treated and untreated wood blocks were exposed under cover in the field against termites for four and the half months. The wood blocks were then evaluated according to the weight loss and termite rating scale. From the result of the study, all untreated and treated wood blocks from three different species showed considerable weight loss. For Shorea macrophylla, there is negligible weight gain for 0.3kglmJ and 0.7kg/mJ target retentions. The termite rating scale of aU treated wood blocks were 10 while for untreated wood blocks only Xylopia sp. showed the rating of9. Due to inconsistent termite feeding in the field, the worst termite rating of the untreated wood species (i.e. Xylopia sp.:7) was chosen to denote the termite susceptibility of the species. Consequently, the termite colonies need more time to suit themselves to the new environment being set up. In contrast, CCA retention value as low as O.3kglmJ may protect the wood from termite attack within the period of four and the half months.